A mixed method study exploring the psychosocial outcomes of outdoor adventure education for adolescents in a South African setting - Blaine, Judith Anne (Rhodes University, Faculty of Humanities, Department of Linguistics and Applied Language Studies)
There is an increasing appreciation that, in order to prepare learners for success in life, they require a holistic education that not only guarantees learning basic academic skills, but also psychosocial competencies that will assist them to become responsible adults and citizens. Some schools and colleges are addressing these objectives by looking for new models and processes to support adolescent development, while also preparing youth to cope and succeed in a rapidly changing and unpredictable future. Outdoor adventure education (OAE) is one such model with previous studies, predominantly in the United Kingdom, Australia and North America, suggesting that OAE is well placed to generate these desired outcomes. Adopting an underlying social constructivist framework, drawing on the theories of experiential learning, the bioecological approach, sociocultural theory, (as well as some aspects of Positive Psychology), this research sought to understand the psychosocial outcomes and perceived value of Journey, a school-based OAE programme, for adolescents in a South African setting. Employing a mixed methods quasi-experimental design, a purposive convenience sample of 184 Grade 10 learners was recruited for this study. Using a four-phase approach to data collection (pre-, during and post- Journey; as well as four months later, adding a longitudinal dimension), this study utilised the Life Effectiveness Questionnaire (Neill, Marsh & Richards, 1997), the Emotional Literacy Questionnaire (Faupel, 2003), the Connor-Davidson Resilience Scale (Connor & Davidson, 2003); as well as focus group interviews and individual semi-structured interviews to explore learners' experiences. Quantitative data were statistically analysed using Analysis of Variance (ANOVA). Quantitative results demonstrated that, after participating in Journey, there were statistically significant increases in self-reports of life effectiveness (F (2, 141) = 12.93, p < 0.001 and resilience (F (2, 1279) = 6.15, p = .002), but not for emotional literacy. Employing template analysis for the qualitative data, the findings are reported using the acronym FLOURISHING. These suggest that Journey, although challenging, was a rewarding undertaking; seemingly beneficial for most of the learners in terms of life skills, intrapersonal skills and interpersonal skills. However, it is noteworthy that not all learners felt that they benefitted from the experience. This study's findings suggest that Journey could possibly be enhanced or modified by adopting a strength-based approach, in an attempt to foster a sense of autonomy, relevance and competence for the participating learners. The importance of the unique contribution of this study to international and South African OAE research is discussed, with recommendations for future research and considerations of the practical implications of the findings.
Keywords: Outdoor education -- South Africa; Teenagers -- South Africa; Resilience (Personality trait) in adolescence; Emotional literacy; Positive psychology; Flourishing